Analisis Penerapan SAP Nomor 1 Tahun 2016 dan PSAK Nomor 1 Tahun 2013 tentang Penyajian Laporan Keuangan pada Badan Penelitian dan Pengembangan Kabupaten Kutai Timur - Sumardi Sumardi; Nuridha Matiin; Juwita Aprillia (Politeknik Negeri Samarinda, 2022)
The presentation of financial statements is carried out on Balitbang Kutim there is no empirical research to see the suitability applied in the agency based on SAP Number 1 of 2016 and PSAK Number 1 of 2013. This study's objective is to find out how SAP Number 1 of 2016 and PSAK Number 1 of 2013 are implemented on the Office of the Research and Development Agency of East Kutai in presenting their financial statements for the period 2015 to 2019. This research uses a qualitative descriptive approach, namely by describing or describing the financial that has been collected as is the application of Government Accounting Standards (SAP) Number 1 of 2016 and PSAK Number 1 of 2013 concerning the presentation of financial statements.